O amor natural e o projeto poético-pensante de Carlos Drummond de Andrade - Dalvi, Maria Amélia (2008)
The reading of O amor natural (1992) (Natural Love) – posthumous book of erotic poems – as the apogee of Carlos Drummond de Andrade’s poético-pensante (thinking-poetic) project. In the construction of the theoretical argumentation, important critical and historical studies about the poet from Minas Gerais are gathered, along with Martin Heidegger’s philosophy in “A origem da obra de arte” (“The Origin of the Work of Art”). In the first chapter, the critical fortune on Drummond’s poetics is reviewed; in the second, the whole of this production is read as a project; in the third, O amor natural (Natural Love) is described and analyzed.